2011
DOI: 10.1038/npp.2011.281
|View full text |Cite
|
Sign up to set email alerts
|

Compound Stimulus Presentation and the Norepinephrine Reuptake Inhibitor Atomoxetine Enhance Long-Term Extinction of Cocaine-Seeking Behavior

Abstract: Drug abstinence is frequently compromised when addicted individuals are re-exposed to environmental stimuli previously associated with drug use. Research with human addicts and in animal models has demonstrated that extinction learning (non-reinforced cue-exposure) can reduce the capacity of such stimuli to induce relapse, yet extinction therapies have limited long-term success under real-world conditions (Bouton, 2002;O'Brien, 2008). We hypothesized that enhancing extinction would reduce the later ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 75 publications
(101 reference statements)
5
39
1
Order By: Relevance
“…However, our results are consistent with prior findings in outbred rats showing that acute administration of methylphenidate did not alter cocaine seeking under a second-order schedule (Economidou et al, 2011). Notably, in outbred rats, NET plays an important role in regulating saliency of drug-associated cues (Economidou et al, 2011; Janak et al, 2012), and therefore be a critical regulator of cue reactivity in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are consistent with prior findings in outbred rats showing that acute administration of methylphenidate did not alter cocaine seeking under a second-order schedule (Economidou et al, 2011). Notably, in outbred rats, NET plays an important role in regulating saliency of drug-associated cues (Economidou et al, 2011; Janak et al, 2012), and therefore be a critical regulator of cue reactivity in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rats are able to learn the negative occasion setting task within 2 wk, well within the timeframe of even the most conservative definitions of adolescence. In addition, negative occasion setting has particular relevance for understanding the role of contextual cues in regulating the emission or omission of behavioral responses (e.g., extinction) (Bouton 1997), which has direct implications for drug seeking and addiction-related behavior (Bouton et al 1990;Conklin and Tiffany 2002;Janak et al 2012), both of which are prevalent during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent drug-cue extinction research suggests ways that this might be accomplished. For example, two studies (Janak, Bowers, & Corbit, 2012; Kearns, Tunstall, & Weiss, 2012) have found that applying a deepened extinction treatment – where the targeted cue is extinguished in compound with another drug cue – significantly enhances the effects of extinction by weakening the cue-drug association to a greater extent than standard extinction. Another recent study has shown that retrieving the cue-drug association (by briefly presenting the cue) during a sensitive window prior to an extinction session can virtually eliminate traces of the association (Xue et al, 2012).…”
Section: Discussionmentioning
confidence: 99%